PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA UNIT USAHA KECIL MENENGAH KOPERASI WANITA X SURABAYA - DIO, YOHANES (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Customer relationship management or commonly known as CRM is a factor that needed by the companies to survive in a competition. UKM units in Koperasi Wanita X also need that if they want to wins the competition. After two weeks observation, that UKM units still haven’t manage a long-term relationship with their special members (anggota luar biasa). By implementing CRM, it expected to be able to recruit their extraordinary members into regular one which have an impact to increase the profitability in UKM units.CRM Value Chain used for implementing CRM in UKM units. It consist five main activities: Customer portfolio analysis, customer intimacy, network development, value proposition, and manage the customer life cycle, also four supporting activities: Leadership and culture, and it is the data, people, and processes.